2009
DOI: 10.1128/jb.00845-08
|View full text |Cite
|
Sign up to set email alerts
|

Erwinia chrysanthemiIron Metabolism: the Unexpected Implication of the Inner Membrane Platform within the Type II Secretion System

Abstract: The type II secretion (T2S) system is an essential device for Erwinia chrysanthemi virulence. Previously, we reported the key role of the OutF protein in forming, along with OutELM, an inner membrane platform in the Out T2S system. Here, we report that OutF copurified with five proteins identified by matrix-assisted laser desorption ionization-time of flight analysis as AcsD, TogA, SecA, Tsp, and DegP. The AcsD protein was known to be involved in the biosynthesis of achromobactin, which is a siderophore import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
1
7
1
Order By: Relevance
“…Our transcriptome profiling and phenotypic analysis demonstrate that inactivation of the T2S system has severe consequences on iron homeostasis and the overall oxidative status of V. cholerae cells. In contrast to previous suggestions for other gram-negative bacteria (17,22), we show that the T2S system is not directly engaged in iron acquisition in V. cholerae.…”
Section: Vol 191 2009 T2s System Iron Homeostasis and Stress Respcontrasting
confidence: 54%
See 2 more Smart Citations
“…Our transcriptome profiling and phenotypic analysis demonstrate that inactivation of the T2S system has severe consequences on iron homeostasis and the overall oxidative status of V. cholerae cells. In contrast to previous suggestions for other gram-negative bacteria (17,22), we show that the T2S system is not directly engaged in iron acquisition in V. cholerae.…”
Section: Vol 191 2009 T2s System Iron Homeostasis and Stress Respcontrasting
confidence: 54%
“…Moreover, it was reported that certain T2S mutants of E. chrysanthemi lack a periplasmic FbpA-like iron binding protein and display increased susceptibility to oxidants and streptonigrin in the stationary phase of growth (17). Our comparative analysis of different T2S and NtolA mutants exhibiting similarly altered outer membrane integrity, however, suggests that changes in iron homeostasis as well as in oxidative stress are not unique to T2S mutants but rather occur in response to cell envelope perturbation.…”
Section: Vol 191 2009 T2s System Iron Homeostasis and Stress Respmentioning
confidence: 56%
See 1 more Smart Citation
“…The modified ferrozine assay demonstrated; however, that the free iron pool was markedly diminished. This observation is in accordance with our previously reported finding that ∆ fupA is highly resistant to streptonigrin [ 9 ], which is considered to be a measure of a small free intracellular iron pool [ 20 , 21 ]. Based on this previous and the present observations, it appears that the poor growth of ∆ fupA probably is not related to heme utilization per se but rather to the role of FupA to maintain an iron pool that is easily accessible to effectively support growth.…”
Section: Discussionsupporting
confidence: 93%
“…We have chosen the phytopathogenic bacterium D. dadantii as our model organism because the structural organization and function of the Out system, as well as its secreted cargo proteins, have been extensively studied. 3,11,14 Moreover, D. dadantii is a causative agent of soft-rot disease in all major groups of dicotyledons and has served as a model in studies elucidating bacterial virulence factors in plant pathogenicity. 5 We reasoned that the delivery of the T2S-exoproteins could be blocked by an inhibitory molecule in multiple ways, including (1) plugging the secretion pore, (2) affecting steps in the assembly of the secretion machinery, (3) disturbing the recognition of the cargo protein by the T2S complex, (4) disrupting interactions between the individual constituents of the T2S complex, (5) interfering with either the Sec or the Tat transport systems located within the cytoplasmic membrane, or (6) inhibiting synthesis of the T2S system (Fig.…”
Section: Design Of the Assay For Screening Of The T2s Inhibitorsmentioning
confidence: 99%